2009
DOI: 10.1002/ejoc.200900664
|View full text |Cite
|
Sign up to set email alerts
|

New Phenylglycine‐Derived Primary Amine Organocatalysts for the Preparation of Optically Active Warfarin

Abstract: In this work we present new, fully synthetic phenylglycine‐derived primary amine organocatalysts useful for the one‐step preparation of optically active warfarin, an important anticoagulant. Both enantiomeric forms of the catalysts are equally available and can be prepared by robust procedures without recourse to chromatographic purification. Together with a co‐catalyst, particularly acetic acid or 2,4‐dinitrophenol, they can furnish warfarin in approximately 80 % ee and represent inexpensive alternatives to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 42 publications
(28 reference statements)
0
28
0
7
Order By: Relevance
“…Very recently, Hansen and co-workers [50] found that diphenylphenylglycinol (77) was an effective catalyst in the Michael addition of 4-hydroxycoumarin (75) to benzylideneacetone albeit with only moderate enantioselectivity and yield. Further exploration showed that the TMS-protected diphenylphenylglycinol (21b) gave a promising higher enantioselectivity (Scheme 24).…”
Section: Active Methylene Compounds As Donormentioning
confidence: 99%
“…Very recently, Hansen and co-workers [50] found that diphenylphenylglycinol (77) was an effective catalyst in the Michael addition of 4-hydroxycoumarin (75) to benzylideneacetone albeit with only moderate enantioselectivity and yield. Further exploration showed that the TMS-protected diphenylphenylglycinol (21b) gave a promising higher enantioselectivity (Scheme 24).…”
Section: Active Methylene Compounds As Donormentioning
confidence: 99%
“…Following this strategy, simple bulky aminoalcohols derived from phenylglycine represent an alternative to other chiral diamines. [58] For a combined mechanism based on covalent/ non-covalent activation, bifunctional catalysts have been developed from previously described vicinal diamines. [ based access to this skeleton, in accordance with the twelve fundamental principles of green chemistry.…”
Section: Amines and Iminesmentioning
confidence: 99%
“…The same group also derived primary amine organocatalysts from amino acid derivatives, such as phenylglycine, to catalyze asymmetric Michael additions. [72] The immobilization of organocatalysts onto polymer supports has been reviewed nicely by Kristensen and Hansen, but the review seems to be focussed primarily on proline and MacMillan-based organocatalysts, leaving room for the attachment of other amino acid-based organocatalysts to polymer supports. [73] A slightly different approach was also taken by Moore et al, using a tyrosinefunctionalized polymer, using the tyrosine as a functional handle on which to attach a MacMillan catalyst.…”
Section: Chiral Materialsmentioning
confidence: 99%